A water-stable homochiral luminescent MOF constructed from an achiral acylamide-containing dicarboxylate ligand for enantioselective sensing of penicillamine. Issue 77 (12th September 2018) - Zhang, Qingfu; Lei, Mingyuan; Kong, Fang; Yang, Yan
Abstract : A water-stable homochiral luminescent MOF was obtained by spontaneous symmetry-breaking crystallization from achiral precursors; it exhibits enantioselective sensing ofd /l -Pen. Abstract : A water-stable homochiral luminescent metal–organic framework (HLMOF), {[Cd(l )(4, 4′-bipy)]·DMA·5H2 O} n (1 ), was obtained by a spontaneous symmetry-breaking crystallization from achiral precursors without any enantiopure auxiliary. The homochirality of1 was confirmed by single-crystal X-ray diffraction and CD spectroscopy. Complex1 exhibits an interesting enantioselective sensing ofd /l -penicillamine in water.